(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
In the history of mankind, we witness a succession of increasingly complex forms of social organization. These are never mere agglomerations of individuals simply by chance, but specific forms of cooperation with a purpose – of collective survival, and, over time, existence in the sense of “good life”, namely of cultural refinement. Through all periods of history, many and diverse forms of organization evolved along these lines. By showing the historical development of such organizations from the antique Greek to the modern nation-state and beyond, this essay will discuss the relationship between “nation”, “state”, “civilization” and “cultural identity” with regards to the contemporary process of globalization.